Linking Leader’s Behavioral Integrity With Workplace Ostracism: A Mediated-Moderated Model - Chaman, Seemab; Shaheen, Sadia; Hussain, Asrar (Frontiers in Psychology, 2022)
Drawing on the social exchange theory and research on leadership influences, we developed and inspected a multilevel model to test the conditions and mechanisms through which a leader’s behavioral integrity deters workplace ostracism. We used trust as a mediator and the narcissistic personality of a leader as a boundary condition in the relationship between a leader’s behavioral integrity and workplace ostracism. Data were collected in three-time lags from N=249 employees working in different five and four-star hotels in Pakistan. The statistical results revealed that a leader’s behavioral integrity reduces workplace ostracism. Additionally, a leader’s behavioral integrity has an indirect effect on workplace ostracism through interpersonal trust. We do not find statistical support for the moderating role of the narcissistic personality of a leader in the relationship between a leader’s behavioral integrity and workplace ostracism. Implications along with limitations and future research directions are also discussed.